Utilization of mathematical processing of retinal images with use of adaptive contrast control (ACC) method to detect quantity of vascular endings - Kolar, P; Starha, P; Vlkova, E (European journal of ophthalmology, 2005)
PURPOSE: The authors investigated whether the method of mathematical processing of retinal images with the use of a computer can be used to evaluate ocular background figures of patients with physiologic retinal findings. This method is based on identification of vascular endings in an examined retinal area. When the authors mention vascular endings, they do not refer to factual endings, but recognizable vascular endings; there are no endings in a vascular system. METHODS: Adaptive contrast control (ACC) method was used to determine a number of vascular endings. The method is based on mathematical processing of a digitized retina picture with the use of a computer. On a digitized retinal picture, the vascular system is identified with the use of the conditional erosion methodology, and the number of vascular endings is then determined. The ACC method was used to process a file of retinal pictures of 38 patients (76 eyes) with physiologic retinal findings. RESULTS: Based on the results of statistical analysis, the authors detected that the number of vascular endings showed a normal curve (Gaussian distribution, p=0.05). A tight correlation between quantities of vascular endings in the right and the left eyes was also detected, which means that the quantity of vascular endings in the right and the left eyes is in a very close correlation (p=0.05). CONCLUSIONS: The authors highlight that the curve of the number of vascular endings of patients with physiologic retinal findings shows a Gaussian distribution.
Keywords: dospělí; Mathematical Computing; funkční lateralita; Female; Adult; Functional Laterality; ženské pohlaví; Adolescent; Image Processing, Computer-Assisted; Retinal Vessels; lidé; Aged, 80 and over; Age Distribution; Male; počítačové zpracování obrazu; Aged; retinální cévy; věkové rozložení; normální rozdělení; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Normal Distribution; Middle Aged; mladiství; matematické výpočty počítačové; Humans